Securing Forest Tenure in Kilifi County, Kenya: Learnings from participatory prospective analysis (PPA) - Mukasa, C.; Tibazalika, A.; Okiror, G.; Wamala, P.; Kagema, F.; Mwangi, E. (2020)
A multi-stakeholder consultative process known as Participatory Prospective Analysis (PPA) proved successful in bringing together stakeholders to find ways to enhance forest tenure security (FTS) in Kilifi County, which was formed in 2010 after a merger of Kilifi and Malindi districts, and is located on the Kenyan coast north of Mombasa. A workshop held in Mombasa in October 2018 brought together actors from government, NGOs, the private sector, community members organized in community forest associations (CFAs), and indigenous leaders.